Bio-inspired intelligence for minimizing losses in substrate integrated waveguide - Souad Akkader; Hamid Bouyghf; Abdennaceur Baghdad (Institute of Advanced Engineering and Science, 2023)
This paper presents a study of various types of losses in substrate-integrated waveguides (SIW) using a genetic algorithm. Three main types of losses are considered and examined separately: conductor loss, dielectric loss, and radiation loss. Furthermore, the current analysis allows for a physical understanding of the loss impacts as well as the creation of design guidelines to reduce losses at 10 GHz frequency while keeping the miniaturized size of the SIW. Validation results obtained using the software Ansys HFSS, verify that the attenuation constant of the SIW can be significantly reduced to 0.4 dB/m, the Insertion loss S21 to -0.2 dB and the return loss to -38 dB if the geometric parameters are chosen properly. This study enables us to identify the source of losses in a SIW and, as a result, eliminate any type of dispersion. That demonstrates the usability of SIW technologies in the design of microwave circuits used in Internet of things applications.